SIGNIFICANCE OF WATER-BODIES IN THE POUMAI CULTURE: A LANDSCAPE ARCHAEOLOGICAL APPROACH - Thiumai, Rex Chawangbou; Manibabu, M.; Philip, Maringmei (ShodhKosh: Journal of Visual and Performing Arts, 2023)
There is a well-known fact that there is always a relationship between the physical setting of the environment and the humans, and the interaction between the two components somehow always leaves a significant remark. Each piece of land may it be water bodies, is deeply embedded with culture specific symbolism, understanding these meanings helps one understand nature-human processes and relationships. In every society, may it be great or little, there is often a myth or oral history related with places that surrounds us. The objective of the study is to reconstruct past human life-ways through both the material and non-material remains of a particular landscape.